2016
DOI: 10.9734/jsrr/2016/26194
|View full text |Cite
|
Sign up to set email alerts
|

Weather Variability and Climate Change Impacts on the Mental Health of a Seaside Community

Abstract: Aims: To assess weather variability and climate change impacts on the mental health of a small fishing community in Sao Paulo, Brazil. Study Design: To this study, a fishing community strongly familiarized with the region was selected. Interviews were held with the most active fishermen members among the community. Place and Duration of Study: Interviews were held in the Association of Mussel Producers and Fishermen of Cocanha's beach (MAPEC), in the municipality of Caraguatatuba, State of Sao Paulo, Brazil, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Our research on Brazilian consciousness has led us to mistrust the expression of anxiety and depression; and the construction of denial or silence, as affirmed by Randall. Research we have carried out (Seixas, 2008;Seixas et al, 2010Seixas et al, , 2012Seixas et al, , 2014Seixas et al, , 2016Seixas & Nunes, 2017), shows a tell-tale picture of unnamed symptoms in the population as a whole that are causing people to seek help from public and private health services. Antidepressants and anti-anxiety medications are being increasingly consumed by the Brazilian population.…”
Section: Climate Change and Subjectivitymentioning
confidence: 99%
“…Our research on Brazilian consciousness has led us to mistrust the expression of anxiety and depression; and the construction of denial or silence, as affirmed by Randall. Research we have carried out (Seixas, 2008;Seixas et al, 2010Seixas et al, , 2012Seixas et al, , 2014Seixas et al, , 2016Seixas & Nunes, 2017), shows a tell-tale picture of unnamed symptoms in the population as a whole that are causing people to seek help from public and private health services. Antidepressants and anti-anxiety medications are being increasingly consumed by the Brazilian population.…”
Section: Climate Change and Subjectivitymentioning
confidence: 99%
“…The first author of this paper carried out the scientific research below. It includes a study of fishing communities in the densely populated municipality of Caraguatatuba -situated in the North Coast region of the State of São Paulo during the last decade (Seixas et al 2016;Seixas et al 2014;Seixas et al 2012). This study was conducted in a geographical area that has undergone significant environmental change over a short time span, degrading the physical and mental health of individual community members with direct impacts on their subjective well-being and quality of life.…”
Section: Establishing Some Links Between Environmental Change Mentalmentioning
confidence: 99%
“…Thus when we analyzed the data from the Brazilian Health System in relation to the mental health of the residents of the municipalities of the North Coast of São Paulo, especially the hospital admissions between 2000 and 2010, there was an unsurprisingly higher than the average rate in Caraguatatuba when compared to the average for state of São Paulo. Interviews with health care professionals further showed that in the same period, from the patients who sought help from mental health services in the municipality, 60% were diagnosed with depression (Seixas et al, 2012;Seixas et al, 2014;Seixas et al, 2016).…”
Section: Establishing Some Links Between Environmental Change Mentalmentioning
confidence: 99%
“…Particularly in certain countries and regions, prolonged and persistent rainy weather can lead to reduced environmental visibility, causing visual recognition difficulties [12]. This results in anxiety and stress among residents [13,14], subtly affecting the visual comfort of urban dwellers and potentially even impacting their psychological health further [2,[15][16][17]. Therefore, in order to enhance the urban visual environment and harness the positive effects of color on perception [18], improving the visual comfort of urban architectural colors in overcast and rainy weather conditions is an urgent issue to be addressed in current urban color planning.…”
Section: Introductionmentioning
confidence: 99%